Phase II study to investigate the efficacy of trastuzumab biosimilar (Herzuma®) plus treatment of physician's choice (TPC) in patients with heavily pretreated HER-2+ metastatic breast cancer (KCSG BR 18–14/KM10B). (October 2022) - Sim, Sung Hoon; Kim, Jeong Eun; Kim, Min Hwan; Park, Yeon Hee; Kim, Jee Hyun; Suh, Koung Jin; Koh, Su-Jin; Park, Kyong Hwa; Kang, Myoung Joo; Ahn, Mi Sun; Lee, Kyoung Eun; Kim, Hee-Jun; et al.
Abstract: We investigated the efficacy and safety of a trastuzumab biosimilar, Herzuma®, in combination with treatment of physician's choice (TPC) in patients with HER2+ metastatic breast cancer (MBC) who had failed at least two HER2 directed chemotherapies. Highlights: Treatment of HER2-positive breast cancer is rapidly evolving with the development of new agents. However, treatment options are still limited after progression with proven anti-HER2 therapies. The combination of chemotherapy with a trastuzumab biosimilar, Herzuma®, was effective and safe in patients with heavily pre-treated HER2+ MBC. Duration of response to previous anti-HER2 therapy, PIK3CA and ERBB2 mutations were associated with clinical efficacies of trastuzumab biosimilar plus chemotherapy.